My heart and other black holes - Warga, Jasmine (2015)
"Seventeen-year-old Aysel's hobby--planning her own death--take a new path when she meets a boy who has similar plan of his own"--
Keywords: Teenagers -- Juvenile fiction; Suicide -- Juvenile fiction; Interpersonal relations -- Juvenile fiction